2021
DOI: 10.1093/femsle/fnab057
|View full text |Cite
|
Sign up to set email alerts
|

Constrictifilum karadense gen. et sp. nov., a new Nostocalean genus from Maharashtra, India

Abstract: A freshwater dwelling cyanobacterium (strain MKW3) was isolated from a sample collected from a water logged sugarcane field located in Malkapur, Karad, Maharashtra, India, and was characterized using a polyphasic approach. In the 16S rRNA gene phylogenetic analysis, strain MKW3 clustered with two misidentified strains—Nostoc sp. CENA239 and Calothrix sp. NIES2100. The phylogenetically related members included strains identified as Nostoc, Aulosira, Calothrix, Tolypothrix, Camptylonemopsis and Microchaete. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“… Amazonocrinis clades I and II did not form a monophyletic cluster in any of the phylogenetic trees inferred in this study (). Moreover, it is also well established that the cut-off values proposed by Yarza et al [34] do not always hold true for the Nostocalean genera and these values should be used judiciously before grouping the taxa [2, 35–38]. The current scenario is another example in which the percentage similarity values prove to be inconclusive in delimiting the generic boundaries in Nostocales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Amazonocrinis clades I and II did not form a monophyletic cluster in any of the phylogenetic trees inferred in this study (). Moreover, it is also well established that the cut-off values proposed by Yarza et al [34] do not always hold true for the Nostocalean genera and these values should be used judiciously before grouping the taxa [2, 35–38]. The current scenario is another example in which the percentage similarity values prove to be inconclusive in delimiting the generic boundaries in Nostocales.…”
Section: Resultsmentioning
confidence: 99%
“…The order Nostocales accommodates all the heterocyte-forming filamentous forms (unbranched, false branched and true branched) of cyanobacteria. The family Nostocaceae, on which the name of the order is based, is one of the largest and widely studied Nostocalean families [1, 2]. The family Nostocaceae includes unbranched filamentous cyanobacteria with isopolar or heteropolar filaments that form heterocytes and akinetes [1].…”
Section: Introductionmentioning
confidence: 99%
“…The 16S rRNA sequences from all strains were included together with 65 reference sequences from public databases to construct a phylogeny. The dataset also included recently described taxa in the order Nostocales, including Amazonocrinis nigriterrae, Dendronalium phyllosphaericum, Constrictifilum karadense , and Atlanticothrix silvestris (Alvarenga et al, 2021 ; Chavadar et al, 2021 ). Phylogenetic trees obtained from ML and BI analyses had similar topologies at the terminal clades.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the percentage similarity of the 16S rRNA gene between the members of both the Amazonocrinis sensu stricto and the Amazonocrinis clade II and the members of the genus Dendronalium ranged from 95.6% to 98.1% (Table S1). However, from many previous studies, it has been well established that the percentage similarity values for demarcating the generic boundaries within the Nostocalean genera do not always satisfy the proposed thresholds and therefore should be used cautiously (Bohunická et al., 2015; Chavadar et al., 2021; Flechtner et al., 2002; Hentschke et al., 2016; Kaštovský et al., 2014; Kumar et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation was encountered in the case of Amazonocrinis wherein the authors identified all the strains as A. nigriterrae , and the ITS region analysis indicated that the strains represented different species (Alvarenga et al., 2021; Kumar et al., 2022). Moreover, it has been previously reported that in certain Nostocalean genera, the ITS region proves to be an efficient tool in differentiating the closely related taxa that could not be delineated using the 16S rRNA gene (Bohunická et al., 2015; Chavadar et al., 2021; Hentschke et al., 2016; Kumar et al., 2022; Pal, Saraf, Kumar, & Singh, 2022; Pal, Saraf, Kumar, Singh, Talukdar, et al., 2022; Shalygin et al., 2017). It must be noted that since the sequence corresponding to the ITS region was available only for D. phyllosphericum CENA369 (type strain), the analysis was conducted between NP‐KLS‐5C‐PS and CENA369 (Figure 10).…”
Section: Discussionmentioning
confidence: 99%